RISIKO USAHATANI PADI PADA WILAYAH BANTARAN SUNGAI CITANDUY (Kasus di Desa Manggungsari, Kecamatan Rajapolah, Kabupaten Tasikmalaya) - Hendar Nuryaman; Faqihuddin Faqihuddin (Universitas Galuh Ciamis, 2020)
Riverbanks are land lines on the left and right side of the river, generally planted with plants whose roots are firmly bound to the ground or also with seasonal crops such as rice, as well as in the citanduy riverbanks. Risk is something that must be faced by anyone, the ability of farmers to manage risk is interesting to learn in order to describe what risks are faced in farming, especially rice. The purpose of this study is to: 1) Identify the types of risks faced by rice farmers; 2) Analyzing the risks of production, costs and income of rice farming; and, 3) Knowing how farmers deal with the risks of rice farming. The study was conducted on 31 rice farmers in Manggungsari Village, Rajapolah District, Tasikmalaya Regency using the Survey Method. The analysis uses descriptive analysis and risk analysis (a Coefficient of Variation/ CV). The results showed that the types of risks faced by farmers in rice farming were disruption of crop pest organisms (pests, diseases and weeds), fluctuations in the price of grain/rice, slow construction of facilities (irrigation, roads, warehouses), damage to equipment production due to continuous use, and the difficulty in finding farm capital loans. Based on the analysis of risk shows that the risk of production, costs and income are categorized low. Furthermore, the method chosen by farmers in dealing with risks before conducting rice farming or experiencing risks, farmers first make a joint plan with farmer groups and agricultural extension workers, during the production period when entering the dry season, more farmers to improve existing waterways for fear of drought land and after run the risk, farmers continue to do their farming while looking for other jobs to earn additional income.